Pattern of hemolysis parameters and association with fetal hemoglobin in sickle cell anemia patients in steady state - Moreira, Juliane Almeida (Rev Bras Hematol Hemoter, 2015)
OBJECTIVE: This study aimed to evaluate the influence of fetal hemoglobin (Hb F) on hemolysis biomarkers in sickle cell anemia patients. METHODS: Fifty adult sickle cell anemia patients were included in the study. All patients were taking hydroxyurea for at least six months and were followed at the outpatient clinic of a hospital in Fortaleza, Ceará, Brazil. The control group consisted of 20 hemoglobin AA individuals. The reticulocyte count was performed by an automated methodology, lactate dehydrogenase and uric acid were measured by spectrophotometry and arginase I by enzyme-linked immunosorbent assay (ELISA). The presence of Hb S was detected by high-performance liquid chromatography. The level of significance was set for a p-value <0.05. RESULTS: A significant increase was observed in the reticulocyte count and lactate dehydrogenase, uric acid and arginase I levels in sickle cell anemia patients compared to the control group (p-value <0.05). Patients having Hb F levels greater than 10% showed a significant decrease in the reticulocyte count, arginase I and lactate dehydrogenase. A significant decrease was observed in arginase I levels in patients taking hydroxyurea at a dose greater than 20 mg/kg/day. CONCLUSION: The results of this study show that sickle cell anemia patients have increases in the hemolysis biomarkers, lactate dehydrogenase, reticulocyte count, arginase I, uric acid and increases in Hb F can reduce the reticulocyte count and arginase I and lactate dehydrogenase levels.